Pengaruh Pendidikan Kesehatan Dengan Tingkat Pengetahuan Dan Sikap Tentang Kekerasan Seksual Pada Mahasiswa - Erika Putri Wulandari; Daeng Putri Bhwa; Yordatumike Tafuli (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
Cases of sexual violence continue to rise annually and cause Indonesia to experience a sexual violence emergency. One of the ways to prevent sexual violence is to Teach to improve knowledge and attitudes towards sexual violence. This study aims to specify the influence of health education on the level of knowledge and attitudes about sexual violence among college students in STIE Oemathonis Kupang. The method used in this study was a quasi-experimental one-group pretest-posttest design. The sampling technique used accidental sampling with sample of 88 people. The study tool operated a questionnaire, and health education utilized a leaflet. The univariate analysis operated by frequency distribution, and bivariate analysis operated the Wilcoxon signed test. The outcomes of the analysis indicated that the level of knowledge in the pretest was 10.8 to 13.22 in the posttest, so there was an increase of 2.41, and the attitude score in the pretest was 44.22 to 51.17 in the posttest, so there was an increase of 6.95. The Wilcoxon test value has a p-value = 0.000 (p <0.05); there is a significant effect between health education and the level of knowledge and attitudes about sexual violence in college students.